2019
DOI: 10.1016/j.nbd.2019.03.001
|View full text |Cite|
|
Sign up to set email alerts
|

Systemic peptide mediated delivery of an siRNA targeting α-syn in the CNS ameliorates the neurodegenerative process in a transgenic model of Lewy body disease

Abstract: Neurodegenerative disorders of the aging population are characterized by progressive accumulation of neuronal proteins such as α-synuclein (α-syn) in Parkinson's Disease (PD) and Amyloid ß (Aß) and Tau in Alzheimer's disease (AD) for which no treatments are currently available. The ability to regulate the expression at the gene transcription level would be beneficial for reducing the accumulation of these proteins or regulating expression levels of other genes in the CNS. Short interfering RNA molecules can bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 112 publications
1
25
0
Order By: Relevance
“…Preclinical studies in rodents and nonhuman primates have successfully shown that α-syn can be down-regulated in PD-affected brain areas after direct application of oligonucleotide therapeutics including antisense oligonucleotides (ASO), small interfering RNAs (siRNA) and microRNAs (miRNA). 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 However, one potential caveat is that in some of the animal model paradigms, a marked α-syn downregulation induced by viral vector-mediated delivery of short hairpin RNA (shRNA) displayed toxicity in nigral dopamine (DA) neurons, thus opposing the potential therapeutic effect. 24 , 25 , 26 , 27 Irrespectively of these potential hitches, a rate-limiting step in the development of oligonucleotide-based therapeutics is the delivery to the brain compartment, and once there, to selected neuronal populations across the lipid bilayer of the cell and endosomal membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical studies in rodents and nonhuman primates have successfully shown that α-syn can be down-regulated in PD-affected brain areas after direct application of oligonucleotide therapeutics including antisense oligonucleotides (ASO), small interfering RNAs (siRNA) and microRNAs (miRNA). 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 However, one potential caveat is that in some of the animal model paradigms, a marked α-syn downregulation induced by viral vector-mediated delivery of short hairpin RNA (shRNA) displayed toxicity in nigral dopamine (DA) neurons, thus opposing the potential therapeutic effect. 24 , 25 , 26 , 27 Irrespectively of these potential hitches, a rate-limiting step in the development of oligonucleotide-based therapeutics is the delivery to the brain compartment, and once there, to selected neuronal populations across the lipid bilayer of the cell and endosomal membranes.…”
Section: Introductionmentioning
confidence: 99%
“…) or siRNA (Spencer et al . ), decreasing α‐syn aggregation with small molecules (Paleologou et al . ; Ardah et al .…”
Section: Therapeutic Strategies In Synucleinopathiesmentioning
confidence: 99%
“…In addition to the continued use of antibodies for research and diagnosis, they are also currently being evaluated as potential therapeutic agents because of their high specificity, high binding affinity, long half lives, and low toxicity. There is no disease-modifying therapy for any synucleinopathy but previous approaches have focused on reducing a-syn expression using antisense oligonucleotides (Murphy et al 2000), miRNA (Junn et al 2009) or siRNA (Spencer et al 2019), decreasing a-syn aggregation with small molecules (Paleologou et al 2005;Ardah et al 2014Ardah et al , 2015Wrasidlo et al 2016), increasing the clearance of a-syn via autophagy (Sarkar et al 2016) and preventing the seeding and prion like spreading of a-syn (Valera et al 2016). Currently, immunotherapeutic approaches are being explored as a potential disease-modifying treatment for synucleinopathies.…”
Section: Therapeutic Strategies In Synucleinopathiesmentioning
confidence: 99%
“…They identified an alternative peptide [apolipoprotein B (ApoB)] which allows the transport of oligonucleotides into the nervous system across the blood brain barrier. This method showed efficacy and revealed reduction of the neuropathological alteration severity in transgenic animal model of Parkinson's disease (Spencer et al 2019).…”
Section: Alpha-synuclein Immunotherapymentioning
confidence: 97%